Adenovirus Transcriptome in Human Cells Infected with ChAdOx1-Vectored Candidate HIV-1 Vaccine Is Dominated by High Levels of Correctly Spliced HIVconsv1&62 Transgene RNA - David A. Matthews; Rachel Milligan; Edmund G. Wee; Tomáš Hanke (Vaccines, 2023)
We develop candidate HIV-1 vaccines, of which two components, ChAdOx1.tHIVconsv1 (C1) and ChAdOx1.HIVconsv62 (C62), are delivered by the simian adenovirus-derived vaccine vector ChAdOx1. Aberrant adenovirus RNA splicing involving transgene(s) coding for the SARS-CoV-2 spike was suggested as an aetiology of rare adverse events temporarily associated with the initial deployment of adenovirus-vectored vaccines during the COVID-19 pandemic. Here, to eliminate this theoretically plausible splicing phenomenon from the list of possible pathomechanisms for our HIV-1 vaccine candidates, we directly sequenced mRNAs in C1- and C62-infected nonpermissive MRC-5 and A549 and permissive HEK293 human cell lines. Our two main observations in nonpermissive human cells, which are most similar to those which become infected after the intramuscular administration of vaccines into human volunteers, were that (i) the dominant adenovirus vector-derived mRNAs were the expected transcripts coding for the HIVconsvX immunogens and (ii) atypical splicing events within the synthetic open reading frame of the two transgenes are rare. We conclude that inadvertent RNA splicing is not a safety concern for the two tested candidate HIV-1 vaccines.